PROBLEMS AND PRESENT CONDITIONS OF GROUND WATER MONITORING IN THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Ground water monitoring in the Republic of Armenia is important to promote sustainable management of ground water resources. That was not conducted during last years. Problems for organizing of observation network for ground water monitoring on the basis of present systematic studies network and also the optimum frequency of measurements and observations during quantitative and qualitative ground water monitoring are considered in the paper.
Keywords: groundwater monitoring; quantitative and qualitative groundwater monitoring; Republic of Armenia